CREATIVE WEB CREATION TRAINING FOR UMKM PARTICIPANTS - Agung Triayudi; Imam Rizqi, Agus Iskandar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to evaluate the effectiveness of creative web creation training in improving the performance of Micro, Small and Medium Enterprises (MSMEs) in Indonesia in facing the digital era. Using a quantitative experimental research design with pre-test and post-test, this research involved 20 MSMEs selected through purposive sampling. Training materials cover web design basics, an introduction to CMS, SEO, and content strategy. Evaluation is carried out by measuring knowledge, skills and business performance before and after training using a questionnaire. The research results show a significant increase in online visibility, website traffic, and increased sales, confirming that creative web training is a valuable investment for MSMEs in increasing competitiveness in the digital market. This study provides insight for policy makers and practitioners about the importance of training programs specifically designed to meet the digitalization needs of MSMEs.